An approach to the Andrés Bello Code’s category of «quasi-delict», from the perspective of Roman classical law’s obligationes quasi ex delicto - Sánchez Hernández, Luis Carlos (2019)
The Civil Code of Andrés Bello, influenced by the French Civil Code, and unlike other European and Latin American codes, included the category of quasi-delict as a source of obligations. However, this notion hasbeen difficult to understand, and has been often branded as merely formal, difficult to define and devoid of any practical utility. For this reason, this paper proposes an analysis of the category of «quasi-delicts» on the basis of the socalled obligations quasi ex delicto in classical Roman law. Such obligations were very useful for the formulation of a perfect and comprehensive division of the sources of obligations. After studying the reception of the quasi-delict in Andres Bello’s Code, both in Chile and in Colombia, this paper proposes some ideas that could contribute to a new understanding of the category and, with it, to the renewal of its systematic and practical utility. The aim of this paper is to highlight the most important aspects of this category that allow for a re-reading of the modern category of quasi-delict in the light of classical Roman categories. For this reason, it would exceed the scope of the present work to carry out an exhaustive exegetical analysis of the entire collection of Roman sources that refer to this matter.